A Comparative Study of the Allocation of Geography Education Resources in Compulsory Education between Urban and Rural Areas: A China–India Case - 苏 洁; 韩宏峰 (New Horizon of Education, 2025)
The allocation of geography education resources in urban and rural compulsory education has far-reaching implications. This article conducts a comparative analysis of the urban–rural education systems in China and India from four dimensions: educational finance, human resources, spatial geography, and cultural institutions. It closely examines the differences in resource allocation at the compulsory education stage between the two countries, identifies the underlying causes, and discusses possible solutions. Through a review of the literature, this study maps the current research progress and highlights both the commonalities and differences between China and India in terms of the structure of financial investment, distribution of teaching staff, geographical accessibility, and cultural acceptance. The findings show that although both China and India face the problem of unequal development between urban and rural education, China’s policy interventions have focused on the redistribution of resources within the formal system, whereas in India, long-standing social stratification and the diversion between public and private education have made structural barriers particularly prominent. Under such circumstances, future efforts to optimize the allocation of urban–rural educational resources must move beyond simple fiscal support and enter a stage of multidimensional governance integrating institutions, space, and culture, so as to draw on useful experience and promote the realization of educational equity.